Images of Kazakh epos, dating back to the mythological concepts and ideas (Herald of Journalism, 2020)
The author, stopping on the functions of fairy-tale motifs in the Kazakh epos, its pays special attention to the nature of artistic images, which are based on mythological ideas. Researcher systematically considered com- mon motifs of fairy tales found in the eastern dastans. It is well known that fighting the enemy forces such as the dragon, divas, witch-mystan, Zheztyrnak and other heroes dastans overcome them. The article presents the views of other scientists on the role of international influence on the formation of motives prevailing in traditional folk stories.
Keywords: epic, mythology, story, detail, fantasy, Dastan, genre, style, image, character, totem, tale.